Caracterização bioquímica, determinação do perfil lipídico e obtenção de extrusados de grãos e farinhas de tremoço branco (Lupinus albus) - Cintia Tarabal Oliveira (2013)
In this work it was developed few steps in the process of obtaining and characterization of nutritionally adequate lupine flour for human consumption. Initially, two flours were prepared (1 and 2) from Lupinus albus grain, varying time (30 min and 60 min) and temperature (100 ° C to 150 ° C) conditions in roasting process in order to assess whether what is the best heat treatment to inactivate the antinutritional factors. It was determined the chemical composition (moisture, lipids, total ash and minerals, soluble and insoluble dietary fiber), trypsin inhibitors and the presence of alkaloids, given that the method applied for the latter two were spectrophotometry and thin layer chromatography respectively. These analyzes were also performed for the raw grain and the pickled lupine sold in stores. Next, the lipid profile of these samples was evaluated by GC after using two different extraction methods (hot and cold) and esterification (acid and base catalysis) of the lipid fraction. Samples of grinded lupine (GL) were then used in the preparation of extruded, associating them with broken rice (BR), in the ratios of 10:90 and 20:80 of TM: QA. The traits analyzed were extruded in IE, IAA, ISA, texture, color and overall appearance by scanning electron microscopy and the raw materials were evaluated by the profile of amino acids, total sugars and the GL starch. The GL and BR grain size were also evaluated. The results indicated that the samples presented high levels of protein (34.14%), lipids (10.6%), and dietary fiber (34%). The greatest amount of the sodium micronutrient was determined in pickled lupine (8744.0 mg / kg), a value much higher than the other samples (451.9 mg / kg). In the case of antinutritional factors it was found amounts of trypsin inhibitors and alkaloids in all the samples studied. Regarding the lipid profile, it consisted of nine fatty acids, there was a predominance of oleic acid (63%). It is also noteworthy that, for all samples, in the ethodologies used in lipid extraction, it wasnt possible to determine significant differences in the quantification of fatty acids. However, through the use of acid catalysis esterification, it was obtained the higher rates of fatty acids. Finally, to evaluate the nutritional properties of the extrudates, it was observed an increase in the content of essential amino acids as the lupine ratio increased in samples. Besides, regarding the technological characteristics, it was observed an increase in the brightness, a reduction in the amounts of IE, ISA and IAA and the color parameter a *, with the addition of larger quantities of this leguminous plant to the mixture. The evaluation of the raw material by scanning electron microscopy identified intact starch granules or pellets, while the extruded samples exhibited a compact mass, amorphous and without apparent starch granules. The study showed that due to the structural modification and the reducing rate of expansion of extrudatescontaining lupine, its use as snacks would be the ideal, however, such samples could be used as pre-gelatinized flour in various products such as instant noodles and soups creating products with better protein profiles.